THE DEVELOPMENT OF MOTRIC QUALITY SPEED AT THE HIGHSCHOOL CYCLE THROUGH THE HANDBALL GAME AT THE TIME OF SPORTS TRAINING - Laurențiu Huțuleac Ilie; Ghervan Petru (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This paper attempts to make a contribution by enriching the methodological material at its disposal (still insufficient) those who opted for the noble mission of initiation in the handball secrets. We have tried to be as close as possible to the practical needs by providing some means mainly focused on the operating structures, by providing to those who are interested in a methodical material that can be processed and adopted under the current conditions. I tried to train the handball team of the "Forestry College of Bucovina" handball to participate in the ONSS competitions and to compete with Stefan cel Mare Military Highschool, the results of this game being not extraordinary, and I think, according to my own opinion, that the training is essential in this game.